1998
DOI: 10.1139/f98-139
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among adult demography, spawning date, growth rate, predation, overwinter mortality, and the recruitment of largemouth bass in a northern lake

Abstract: Using 12 years of data, we evaluated the mechanisms controlling largemouth bass, Micropterus salmoides, recruitment in a lake near the northern extent of the largemouth bass range. We found that complex interactions among adult demographics, size-selective predation, and overwinter mortality regulate the number of largemouth bass surviving the first year of life. The largest recruitment events required at least a moderate number of adults, but a large number of adults was not sufficient to produce a large coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
37
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(43 citation statements)
references
References 45 publications
6
37
0
Order By: Relevance
“…Larval density was correlated with the number of spawning adults (Post et al 1998), a result similar to our study. Different from our study, however, the number of recruits was unrelated to larval density (Post et al 1998); rather, spawning date and growth rate influ- enced the probability of predation and overwinter mortality, and these processes interacted to regulate first-year survival (Post et al 1998). Another study sampled several life history stages of brown trout Salmo trutta and found egg density to be a strong predictor of the number of survivors in five subsequent life history stages (Elliott 1985).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Larval density was correlated with the number of spawning adults (Post et al 1998), a result similar to our study. Different from our study, however, the number of recruits was unrelated to larval density (Post et al 1998); rather, spawning date and growth rate influ- enced the probability of predation and overwinter mortality, and these processes interacted to regulate first-year survival (Post et al 1998). Another study sampled several life history stages of brown trout Salmo trutta and found egg density to be a strong predictor of the number of survivors in five subsequent life history stages (Elliott 1985).…”
Section: Discussionsupporting
confidence: 90%
“…Sampling multiple life history stages allows for determination and confirmation of when year-class strength is set and, in turn, allows for hypothesis generation of the important mechanisms. For largemouth bass Micropterus salmoides, the number of spawning adults, nests, newly hatched larvae, juveniles, and recruits were sampled for 12 years in Paul Lake, Michigan (Post et al 1998). Larval density was correlated with the number of spawning adults (Post et al 1998), a result similar to our study.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In contrast, there is hardly any evidence for dynamic trophic cascades, in which major shifts in overall food-web structure are intrinsically driven by population dynamics. Only a few studies on recruitment variation have considered this aspect (10)(11)(12).…”
mentioning
confidence: 99%